Rejuvenating the Aging Heart by Enhancing the Expression of the Cisd2 Prolongevity Gene - Chi-Hsiao Yeh (MDPI AG, 2021)
Aging is the major risk factor for cardiovascular disease, which is the leading cause of mortality worldwide among aging populations. Cisd2 is a prolongevity gene that mediates lifespan in mammals. Previously, our investigations revealed that a persistently high level of Cisd2 expression in mice is able to prevent age-associated cardiac dysfunction. This study was designed to apply a genetic approach that induces cardiac-specific Cisd2 overexpression (Cisd2 icOE) at a late-life stage, namely a time point immediately preceding the onset of old age, and evaluate the translational potential of this approach. Several discoveries are pinpointed. Firstly, Cisd2 is downregulated in the aging heart. This decrease in Cisd2 leads to cardiac dysfunction and impairs electromechanical performance. Intriguingly, Cisd2 icOE prevents an exacerbation of age-associated electromechanical dysfunction. Secondly, Cisd2 icOE ameliorates cardiac fibrosis and improves the integrity of the intercalated discs, thereby reversing various structural abnormalities. Finally, Cisd2 icOE reverses the transcriptomic profile of the aging heart, changing it from an older-age pattern to a younger pattern. Intriguingly, Cisd2 icOE modulates a number of aging-related pathways, namely the sirtuin signaling, autophagy, and senescence pathways, to bring about rejuvenation of the heart as it enters old age. Our findings highlight Cisd2 as a novel molecular target for developing therapies targeting cardiac aging.